Analisis Sistem Informasi Akuntansi Persediaan Barang Dagang Pada Umama Super Store Cabang Purwakarta - Dena Nurul Afifah; Nunung Aini Rahmah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the accounting information system for trade goods inventory. The object of this research is the accounting information system for trade goods inventory. The research method used in this research is a qualitative research method with a case study approach and the data collected consists of primary and secondary data. Primary data is collected through interviews and observations while secondary data is obtained through library research. The results of this study indicate that the hardware is running very well, the software is running well, human resources are running well, the procedures are running quite well, the database is running very well, the communication network is running well, the control is running poorly, and the purpose of the inventory accounting information system is running poorly. So, the conclusion from the results of this study is that the accounting information system for trade goods inventory at Umama Super Store Purwakarta Branch is running well Keywords: Accounting Information System, Inventory, Merchandise